Transcriptome-Wide N6-Methyladenosine Methylome Alteration in the Rat Spinal Cord After Acute Traumatic Spinal Cord Injury - Yu, Jiangtao; Chen, Haihua; Ma, Haoli; Zhang, Zhongxiang; Zhu, Xiaolu; Wang, Pengcheng; Liu, Ruining; Jin, Xiaoqing; Zhao, Yan (Frontiers in Neuroscience, 2022)
As an important part of epigenetics, N6-methyladenosine (m6A) is gradually discovered to play an important role in neurological diseases. We use methylated RNA immunoprecipitation sequencing (MeRIP-Seq) technology to outline the m6A modification map after traumatic spinal cord injury. A total of 2609 differential m6A peaks were identified after TSCI. The RNA sequencing results of SCI showed a total of 4206 genes with significantly altered expression. Cross-link analysis of m6A sequencing results and RNA sequencing results, the results showed that 141 hyper-methylated genes were up-regulated, 53 hyper-methylated genes were down-regulated, 57 hypo-methylated genes were up-regulated, and 197 hypo-methylated genes were down-regulated. Among which, the important inflammatory response factor TLR4 and the important member of the neurotrophin family NGF are up-regulated and hyper-methylated after TSCI. This study provided research data for the future study about epigenetic modifications of genes response to TSCI.